Advances of Congenital Alopecia/Hypotrichosis in Genetics Research - CUI Can; CHEN Xi; WEI Aihua (罕见病研究, 2023)
Congenital alopecia/hypotrichosis is a rare group of monogenic genetic hair disorders characterized by congenital limited or diffuse hair loss and scarcity, without any effective treatment. Genetic testing to identify the causative gene mutation is the gold standard for confirming the diagnosis of this group of disorders. Because of the heterogeneity in clinical features and genetic pattern of this group of diseases, it is very easy to misdiagnose and mistreat them as diffuse baldness or androgenic alopecia and other acquired alopecia, so clinicians should improve their understanding of this group of diseases. With the continuous development of molecular biology techniques in recent years, a variety of causative genes for congenital alopecia/hypotrichosis have been identified so far, and the pathogenesis of some of these genes and their corresponding subtypes have been clarified. In this paper, we reviewed the clinical manifestations and genetic research progress of non-syndromic congenital alopecia/ hypotrichosis, in order to facilitate clinicians' comprehensive understanding of these rare hair diseases and improve clinical diagnosis and treatment.